Perspectiva constitucional del periodo de prueba en el contrato de trabajo indefinido de apoyo a los emprendedores - Gallego Moya, Fermín (Revista de Derecho, 2020)
One of the most significant legislative reforms in labour the last five years in Spain has been the creation of a new type of a permanent contract that supports the entrepreneurs (art. 4.3 of Law 3/2012), whose main feature is the attachment of a trial period, with an unchangeable and a short duration of one year, with no relation whatsoever of the professional category or task performed by the recipients of the regulation. With the growing doctrinal controversy and distinctive judicial pronouncements against a figure that, seemingly, diverges from that very purpose of the trial period, an urgent ruling was made necessary by the Constitutional Court, which has occurred through three important judgments, that validates the reform and aims for the verification of the economic viability of the job as a “new” foundation of the trial period in this contract. We dedicate our commentary to the analysis of the last of these judgments, with which, finally, the question is closed, at least within our borders/limits. It happens, however, that in the High Court rulings also exist, for now minority, opposite to the constitutionality of the regulation, as well as a judicial power that postulates the derogation from that norm, in response to international precepts and to Community law, so, no doubt, this is an open question.